2014
DOI: 10.1194/jlr.m049429
|View full text |Cite
|
Sign up to set email alerts
|

A novel posttranscriptional mechanism for dietary cholesterol-mediated suppression of liver LDL receptor expression

Abstract: The expression of liver LDL receptor (LDLR) regulates human plasma LDL-cholesterol (LDL-C) homeostasis ( 1-3 ). Increased hepatic LDLR expression results in improved clearance of plasma LDL-C through receptor-mediated endocytosis, which is strongly associated with a decreased risk of developing cardiovascular disease in humans ( 4, 5 ). Thus far, many studies have demonstrated that intracellular cholesterol levels play a primary role in determination of hepatic LDLR expression levels through a negative feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…However, signifi cant reductions in hepatic PCSK9 mRNA expression and serum PCSK9 concentrations were only observed in the Ad-shHNF1 ␣ virusinfected animals. Of note is that the infection dose of 4-6 × 10 9 PFU/animal and timeline (7-10 days postinfection) of analysis is consistent with other reports using adenoviral delivery vectors to knockdown gene expression in murine livers (33)(34)(35). Consistent with in vitro results, in vivo knockdown of HNF1 ␤ did not result in repression of hepatic PCSK9 mRNA levels.…”
Section: Hepatic Hnf1 ␤ Knockdown Increased Serum Pcsk9 Levels In Micesupporting
confidence: 80%
“…However, signifi cant reductions in hepatic PCSK9 mRNA expression and serum PCSK9 concentrations were only observed in the Ad-shHNF1 ␣ virusinfected animals. Of note is that the infection dose of 4-6 × 10 9 PFU/animal and timeline (7-10 days postinfection) of analysis is consistent with other reports using adenoviral delivery vectors to knockdown gene expression in murine livers (33)(34)(35). Consistent with in vitro results, in vivo knockdown of HNF1 ␤ did not result in repression of hepatic PCSK9 mRNA levels.…”
Section: Hepatic Hnf1 ␤ Knockdown Increased Serum Pcsk9 Levels In Micesupporting
confidence: 80%
“…As we expected, whereas HNF1␣ mRNA levels were barely changed by any of the treatments, PCSK9 mRNA expression levels were reduced by BBR and increased by BTZ without or with BBR, which was consistent with the results of Western blot analysis. It is worthy to note that our previous studies have demonstrated that BBR increases LDLR mRNA levels by mRNA stabilization mediated through the LDLR mRNA 3Ј-untranslated region (17,20), and this BBR effect was not affected by the proteasome inhibitor. BTZ treatment did not alter LDLR mRNA levels in uninduced control cells or in BBR-stimulated cells.…”
Section: Evaluation Of Autophagy-lysosomal Pathway and Ubiquitin Protmentioning
confidence: 83%
“…Animal Diet and BBR Treatment-2-3-month-old FVB mice expressing a luciferase reporter gene (20) were used in the BBR study. The expression of the luciferase in these mice is irrelevant to this study.…”
Section: Methodsmentioning
confidence: 99%
“…The increased hepatic fatty acids levels may fuel the pool of acetyl-CoA, an important metabolic branch point, as a source for both ketone body production and hepatic cholesterol synthesis (13), with the latter associated with higher HMG-CoA reductase activity and hepatic total cholesterol levels. As hepatic levels of cholesterol regulate LDL receptor expression (14,15), empagliflozin treatment lowered LDL receptor expression and plasma LDL-C catabolism, which in turn increased LDL-C plasma levels. Although a raise in LDL-C levels is seen as an increase in cardiovascular event risk (16), it is probably not so prominent with empagliflozin.…”
Section: Discussionmentioning
confidence: 99%